Ligation of Intersphincteric Fistulous Tract versus Fistulotomy in Low Trans-Sphincteric Perianal Fistula - Hend Ahmed Hassan ELtairy *; Mahmoud Abdelhameid Mahmoud; Mohammed Ahmed Omar; Mohamed Ahmed Negm; Mahmoud A. A. Abozeid (SVU - International Journal of Medical Sciences, 2024)
Background: Anal fistula, which causes periodic swelling and pain in the perianal area followed by spontaneous leakage, is an abnormal connection between the anal canal and the perianal skin. The majority are connected to the development of abscesses, with a perianal fistula existing at the time of presentation in one-third of patients with an anorectal abscess. Objectives: to determine the safety and efficacy of the Ligation of Intersphicteric Fistulous Tract operation (LIFT) in comparison with fistulotomy. Patients and methods: On 60 patients with low trans-sphincteric perianal fistulas, this prospective, randomized comparative research was done at the General Surgery Department of Qena Faculty of Medicine. Patients were split into two groups: Group (A): 30 patients underwent LIFT techniques. Group (B): 30 patients underwent fistulotomy. The duration of the study ranged between 6-12 months, Results: Body Mass Index (BMI) was statistically substantial greater in patients treated by LIFT than those treated by fistulotomy. While pain score and healing time were statistically substantial lower in patients treated by LIFT than those treated by fistulotomy. There is no statistically substantial variation between patients treated by fistulotomy and LIFT as regard the development of complications as recurrence or incontinence. Conclusion: In comparison to open fistulotomy, the LIFT operation is a successful and preferred sphincter-saving method for fistula-in-ano, with a quicker healing period and a decreased frequency of postoperative anal leakage.